Helicopter blade morphing strategies aimed at mitigating environmental impact | Strategie aktywnego kształtowania profilu łopat helikoptera w celu redukcji negatywnego wpływu ich pracy na środow - Pagano, Antonio; Ameduri, Salvatore; Cokonaj, Valerijan; Prachǎr, Ales; Zachariadis, Zacharias; Drikakis, Dimitris (Polish Society of Theoretical & Applied Mechanics, 2011)
The requirement of mitigating the environmental impact of helicopters has been addressed globally within the FRIENDCOPTER Project in the sen- se that several aspects (such as noise abatement, vibration reduction, fuel consumption) have been studied in parallel with different approaches among which there is the active blade control. In the work at hand, attention is paid on two topics aimed at mitigating helicopter environmental impact through a morphing strategy: the aerodynamic optimization of a blade section who- se camber can be affected by an actuator and the design of a SMA based static twist concept, aimed at extending the helicopter flight envelope. The latter device is based on a SMA rod which is integrated in the spanwise di- rection within the blade structure at different positions. The actuator, when heated, transmits a torque couple which induces twist onto the blade. The twist variation due to the SMA device activation has been predicted by a FE approach (MSC/Marc software implemented with the SMA Brinson model). Finally, rotor performance in hover has been estimated with the actuator in power on and off positions, highlighting benefits coming from several spanwise integrations/distributions of the SMA device.